Clinical study in genital herpes: natural Gene-Eden-VIR/Novirin versus acyclovir, valacyclovir, and famciclovir - Polansky H; Javaherian A; Itzkovitz E (Dove Medical Press, 2016)
Hanan Polansky, Adrian Javaherian, Edan Itzkovitz The Center for the Biology of Chronic Disease (CBCD), Valley Cottage, NY, USA Background: This paper reports the results of a clinical study that tested the effect of suppressive treatment with the botanical product Gene-Eden-VIR/Novirin on the number of genital herpes outbreaks. The results in this study were compared to those published in clinical studies of acyclovir, valacyclovir, and famciclovir. Methods: The framework was a retrospective chart review. The population included 139 participants. The treatment was one to four capsules of Gene-Eden-VIR/Novirin per day. The duration of treatment was 2–48 months. The study included three controls recommended by the US Food and Drug Administration (FDA): baseline, no treatment, and dose response. Results: The treatment decreased the number of outbreaks per year in 90.8% of the participants. The treatment also decreased the mean number of outbreaks per year from 7.27 and 5.5 in the control groups to 2.39 (P<0.0001 and P<0.001, respectively). The treated participants reported no adverse experiences. Out of the 15 tests that compared Gene-Eden-VIR/Novirin to the three drugs, Gene-Eden-VIR/Novirin had superior efficacy in eight tests, inferior efficacy in three tests, and comparable efficacy in four tests. Gene-Eden-VIR/Novirin also had superior safety. Conclusion: The clinical study showed that the natural Gene-Eden-VIR/Novirin decreases the number of genital herpes outbreaks without any side effects. The study also showed that the clinical effects reported in this study are mostly better than those reported in the reviewed studies of acyclovir, valacyclovir, and famciclovir. Keywords: acyclovir, valacyclovir, famciclovir, natural treatment, genital herpes, outbreaks